A Comprehensive performance evaluation and ranking methodology under a sustainable development perspective - Hsu, Li-Chang; Ou, Shang-Ling; Ou, Yih-Chang (Journal of Business Economics and Management, 2014)
Under industry globalization and the intensely competitive environment, a company’s competitiveness must constantly be upgraded in order to achieve the goal of sustainability. Therefore, the correct and valid evaluation of companies’ sustainable performance has become an important issue. The main purpose of this study is to discuss and establish a sustainable performance evaluation criteria and model for companies. First, the measurements of companies’ financial, credit risk, environmental and social responsibility are integrated to create sustainable business performance evaluation criteria. Then, we integrate grey relational analysis and an improved TOPSIS method to construct a sustainable performance evaluation model for companies. In order to verify the findings of this study, we adopt Taiwan’s high-tech listed companies as the research object to explore sustainable operating performance and ranking in 2011. The empirical results will help companies to build future business strategies and can also be used as an important reference for investor and bank credit auditing.